Determinationfo ‏‎ Anti-mürellian Hormone and ‎Vitamin D in Breast Cancer Patients (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Anti-mürellian hormone and Vitamin D in patients with proven breast cancer have been estimated to find the possibility of using such parameters as biomarkers in the diagnosis of breast cancer patients compared to control.Sera of (32) patients had been taken to estimate the levels of [AMH] & [VIT.D] at the period (March/2017-Julyl/2017). All studied patients samples were female with the range age (30-41) years. The present results showed a significant difference in statistic results at (P